Trade Liberalization in China's Accession to the World Trade Organization - Ianchovichina, Elena; Martin, Will (World Bank, Washington, DC, 2014)
Before reform, China's trade was dominated by a few foreign trade corporations with monopolies on the trade of specific ranges of products. Planners could control imports through these corporations so there was little need for conventional instruments such as tariffs, quotas, and licenses. Trade reforms increased the range of enterprises eligible to trade in specific commodities and led to the development of indirect new trade instruments, such as duty exemptions. Duty exemptions almost completely liberalized the imports of intermediate inputs used to produce exports and investment goods used in joint ventures with foreign enterprises. Comprehensive liberalization measures in China's World Trade Organization (WTO) accession package will help ease this problem as tariff reduction reduces the costs of domestic inputs to exporters. WTO commitments will also lead to the abolition of most nontariff barriers and of quotas on textiles and clothing. With accession, China's share of world exports may almost double between 1995 and 2005 - an estimate that is smaller than those found in studies that do not incorporate duty exemptions. (Duty exemptions were a form of partial liberalization, so any further reduction in protection will boost trade volume less than some estimate.) With reform, labor-intensive industries are expected to grow most, especially exports of apparel. Wages of unskilled worker should rise.